Study of the electrosynthesis of hollow rectangular microtubes of polypyrrole - González, Belén (2012)
Hollow rectangular-sectioned microtubes of polypyrrole were deposited on stainless steel by potentiostatic electropolymerization of pyrrole in the presence of an aqueous solution of salicylate. The formed films were characterized using AFM, SEM, EDS, UV and IR spectroscopies, XRD and XPS analysis methods. The initial crystallization of salicylic acid is considered to be responsible for the formation of these special morphological structures. The experimental results indicate a high content of salicylic acid and salicylate in the electrosynthesized film. The microtubes of the polymer doped with salicylate anions coexist with the acid. PPy microtubes remain on the electrode surface after extraction of the acid from the film with ethanol.